Manajemen Strategi Kepala Madrasah Dalam Membangun Budaya Religius Di Lingkungan Madrasah Aliyah Negeri 2 Padangsidimpuan - Siti Rahma Dongoran (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2023)
The aim of this research is to describe the religious culture in the Madrasah Aliyah Negeri 2 Padangsidimpuan environment, and to describe the strategic management of the madrasa head in building religious culture in the Madrasah Aliyah Negeri 2 Padangsidimpuan environment. This research uses a qualitative method with a descriptive approach. The primary data for this research was obtained directly from interviews with the head of Madrasah Aliyah Negeri 2 Padangsidimpuan, for secondary data in this research in the form of photos, documents and videos during the research. Data collection techniques were carried out using observation, interviews and documentation. Data analysis in this research is by data reduction. The triangulation method was used to check the validity of this research data. Data validity checking method that uses something different from the data for checking or comparison. According to the results of the research, religious culture in Madrasah Aliyah Negeri 2 Padangsidimpuan includes holding morning assembly, reading prayers and verses from the Koran before starting lessons, getting used to praying Dhuha and midday prayers in congregation, and carrying out Islamic activities. And the strategic management of the madrasa head in developing religious culture at Madrasah Aliyah Negeri 2 Padangsidimpuan is by having planning, partnership, habituation, organizing, directing, monitoring and evaluating